Oleuropein Improved Post Cerebral Stroke Cognitive Function by Promoting Histone Acetylation and Phosphorylation of cAMP Response Element-Binding Protein in MCAO Rats. Issue 3 (20th August 2020) - Gao, Yang; Li, Xiaojin; Xu, Rongjian; Guo, Yan; Yin, Haiyan; Tan, Ruifeng; Qi, Ze; Liu, Guangzhe; Liang, Jiahui; Ya, Bailiu
Background: Post-stroke cognitive impairment (PSCI) is commonest clinical disorder in which peripheral cholinergic activity is important. Oleuropein (OLP) is polyphenol is present in olive oil. Here we evaluated the effect of OLP in cognitive dysfunction rats in post cerebral stroke model. Methods: The post cerebral stroke cognitive dysfunction PSD rat model was created by occlusion of transient middle cerebral artery. The rats were divided into 6 groups named, Sham + Vehicle, Sham + OLP (50 mg/kg), PSD rats + Vehicle, PSD rats + OLP (20, 50 or 100 mg/kg). The spatial learning was assessed by Morris water maze (MWM). The expression of choline acetyltransferase (ChAT), acetylcholine (ACH), extent of histone acetylation and phosphorylation of cAMP response element-binding protein (CREB) were evaluated by Western blot assay and immunofluorescence staining. Results: Treatment of OLP at various doses showed higher number of spontaneous and rewarded alterations and lesser percentage bias compared to vehicle treated PSD rats. OLP resulted in decreased levels of ChAT and ACH, whereas the degree of histone acetylation and phosphorylation of CREB improved in dose dependent pattern. Conclusion: treatment of OLP improved PSCI via increasing the phosphorylation of CREB and histone acetylation, thus attenuating cholinergic activity.